Design of hybrid field beamforming scheme for STAR-RIS-aided communication systems - SHAO Kai; WANG Hongyu; WANG Guangyu (Tongxin xuebao)
A beamforming design scheme was proposed based on simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) communication systems. To address the hybrid near-far field challenges induced by extremely large-scale antenna arrays (ELAA), a hybrid channel model based on array steering vectors was established first. Subsequently, a hybrid clustering strategy for far-near field users based on hybrid non-orthogonal multiple access (H-NOMA) and a serial interference cancellation (SIC) scheme at the receiving end were proposed to match far-near field users according to the channel strength from STAR-RIS to users. Through joint optimization of beamforming vectors and STAR-RIS phase shift matrices, a suboptimal solution was derived for the max-min total rate optimization problem. Simulation results demonstrate the superior performance of the proposed scheme in hybrid scenarios, where STAR-RIS and H-NOMA effectively enhance system performance. Compared with conventional passive RIS, orthogonal multiple access (OMA), and far-field channel modeling approaches, the proposed scheme achieves 220.9%, 71.2%, and 23.4% improvements in max-min total rate, respectively.